2016
DOI: 10.1111/bjh.13903
|View full text |Cite
|
Sign up to set email alerts
|

Late mortality, secondary malignancy and hospitalisation in teenage and young adult survivors of Hodgkin lymphoma: report of the Childhood/Adolescent/Young Adult Cancer Survivors Research Program and the BC Cancer Agency Centre for Lymphoid Cancer

Abstract: Late complications affecting Hodgkin lymphoma (HL) survivors are well described in paediatric and adult-based publications. This study determined the late morbidity and mortality risk for 442 teenage and young adult (TYAs) 5-year HL survivors, diagnosed at 15-24 years of age between 1970 and 1999, identified from the British Columbia Cancer Registry. Treatment details were abstracted from charts. Survivors and a matched comparison cohort were linked to provincial administrative health datasets until December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 68 publications
4
51
1
Order By: Relevance
“…Since OS did not differ between the groups with the available follow-up time, this study calls for the need of investigating the occurrence of late effects, such as hospitalization [21], secondary AML [22], breast cancer and other secondary malignancies [23,24] heart and lung diseases [25], future fertility [26] and the risk of sick leave and disability pension [27] between children and adults receiving different treatment concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Since OS did not differ between the groups with the available follow-up time, this study calls for the need of investigating the occurrence of late effects, such as hospitalization [21], secondary AML [22], breast cancer and other secondary malignancies [23,24] heart and lung diseases [25], future fertility [26] and the risk of sick leave and disability pension [27] between children and adults receiving different treatment concepts.…”
Section: Discussionmentioning
confidence: 99%
“…One other study has done so18 but, as it was based on only 281 individuals, it was unable to provide risk estimates with any precision. Several studies of cause‐specific mortality in survivors of Hodgkin lymphoma diagnosed in childhood or early adult life have been carried out,19, 20, 21 and the risk of hospitalisation among survivors of all types of cancer diagnosed in adolescence and young adulthood has been studied in other populations 22, 23, 24, 25.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3). Several other studies have reported increases in incidence or mortality from infections either in survivors of Hodgkin lymphoma,9, 18 or in broader groups of cancers diagnosed in teenagers and young adults22, 24, 25 but none of these studies has revealed the extent of the disease burden from infections, as they have all considered only infections classified in Chapter II of the ICD, rather than bringing together all infections irrespective of where they appear in the ICD.…”
Section: Discussionmentioning
confidence: 99%
“…9 Secondary malignancies are one of the most relevant causes for mortality in Hodgkin's lymphoma survivors. 27 Secondary leukaemia and myelodysplastic syndromes are associated with combination chemotherapy, especially etoposide in a dose-dependent manner. Etoposide-related leukaemia is distinguished from other forms of leukaemia that can be induced by alkylating agents by characteristics such as a shorter time from the end of treatment to development of leukaemia and evidence of translocation 11q23 or 21q22.…”
Section: Multiple Primaries In Patients With Prostate Cancermentioning
confidence: 99%